ETHANOPHARMACOLOGICAL STUDY OF CYPERUS ROTUNDUS - A HERB USED BY TRIBAL COMMUNITY AS A TRADITIONAL MEDICINE FOR TREATING VARIOUS DISEASES. - Jain, Pushpendra Kumar; Das, Debajyoti (Innovare Journal of Ayurvedic Sciences, 2016)
ABSTRACT The purpose of this article is to study and to verify the therapeutic effects and margin of safety of traditional medicines used by tribal community for treating various diseases as described in ancient literature found in our country. Herbs have been important contributors to the quality of human life for thousands of years. Herbal medicine is the oldest and most widely used form of medicine in the world today. Throughout history plants have served mankind as valuable components of seasonings, teas, cosmetics, dyes and medicines. Medicinal plants have a traditionally important position in the socio-cultural, spiritual and medicinal arena of rural and tribal lives throughout the world, India is rich in indigenous herbal resources due to its diverse climatic and soil conditions and multiple ecological regions. In Himalayan region of India more than 2000 medicinal plant species exist. Although medicinal plants have been used since long, their scientific substantiation has recently been initiated. Looking into the steady expansion in the global population and prevalence of various diseases, such studies are the need of time to ensure availability of drugs in sustainable manner from natural sources for future generations. Based on therapeutic and commercial importance of medicinal plants, the Cyperus rotundus has been undertaken to evaluate various ethanopharmacological parameters, as it has been used by number of tribal communities in Central part and Southern part of India. According to WHO estimates about 80% of the of the world's population (mostly in developing countries) rely on traditional medicine, almost plant based drugs, for their primary health care needs .Plants products also play an important role in the health care systems of the remaining 20% of population residing in developed countries. Currently, at least 122 phyto-constituents, derived from 94 plant species, can be considered as important drugs that are in use in one or more countries as therapeutic agents. KEYWORDS: Traditional medicines; ethanopharmacological; phytoconstituents; diseases; medicinal plants; herbal medicines; nautral resources; tribal communities; cosmetics; dyes; therapeutic agents.